DISTAG/TBCCd1 Is Required for Basal Cell Fate Determination in Ectocarpus . Issue 12 (5th December 2017) - Godfroy, Olivier; Uji, Toshiki; Nagasato, Chikako; Lipinska, Agnieszka P.; Scornet, Delphine; Peters, Akira F.; Avia, Komlan; Colin, Sebastien; Mignerot, Laure; Motomura, Taizo; Cock, J. Mark; Coelho, Susana M.
Abstract : Mutations in Ectocarpus DISTAG, which encodes a TBCCd1 protein, disrupt the subcellular architecture in the germinating initial cell leading to loss of all basal structures from the developing alga. Abstract: Brown algae are one of the most developmentally complex groups within the eukaryotes. As in many land plants and animals, their main body axis is established early in development, when the initial cell gives rise to two daughter cells that have apical and basal identities, equivalent to shoot and root identities in land plants, respectively. We show here that mutations in the Ectocarpus DISTAG ( DIS ) gene lead to loss of basal structures during both the gametophyte and the sporophyte generations. Several abnormalities were observed in the germinating initial cell in dis mutants, including increased cell size, disorganization of the Golgi apparatus, disruption of the microtubule network, and aberrant positioning of the nucleus. DIS encodes a TBCCd1 protein, which has a role in internal cell organization in animals, Chlamydomonas reinhardtii, and trypanosomes. Our study highlights the key role of subcellular events within the germinating initial cell in the determination of apical/basal cell identities in a brown alga and emphasizes the remarkable functional conservation of TBCCd1 in regulating internal cell organization across extremely distant eukaryotic groups.